Randomized comparison of chloroquine plus sulfadoxine-pyrimethamine versus artesunate plus mefloquine versus artemether-lumefantrine in the treatment of uncomplicated falciparum malaria in the Lao People's Democratic Republic. - Mayxay, M; Khanthavong, M; Lindegårdh, N; Keola, S; Barends, M; Pongvongsa, T; Yapom, R; Annerberg, A; Phompida, S; Phetsouvanh, R; White, N; Newton, P (2004)
BACKGROUND: Recent clinical trials in the Lao People's Democratic Republic have demonstrated that chloroquine and sulfadoxine-pyrimethamine, which are national malaria treatment policy, are no longer effective in the treatment of uncomplicated Plasmodium falciparum malaria. METHODS: A randomized comparison of 3 oral antimalarial combinations--chloroquine plus sulfadoxine-pyrimethamine versus artesunate plus mefloquine versus artemether-lumefantrine--with 42-day follow-up period, was conducted among 330 patients with acute uncomplicated falciparum malaria in southern Laos. RESULTS: The 42-day cure rates, as determined by intention-to-treat analysis and adjusted for reinfection, were 100%, 97%, and 93% for the groups receiving artesunate plus mefloquine, artemether-lumefantrine, and chloroquine plus sulfadoxine-pyrimethamine, respectively. Of 8 patients receiving chloroquine plus sulfadoxine-pyrimethamine who experienced treatment failure, 6 had early treatment failure. The mean parasite clearance time was significantly longer in patients treated with chloroquine plus sulfadoxine-pyrimethamine (2.9 days; 95% confidence interval [CI], 2.8-3.0 days) than in those treated with artesunate plus mefloquine (2.07 days; 95% CI, 2.0-2.1 days; P<.001) and artemether-lumefantrine (2.08 days; 95% CI, 2.0-2.1 days; P<.001). Cure rates with artemether-lumefantrine were high despite low mean daily dietary fat intake (13.8 g; 95% CI, 12.5-15.1 g) and day 7 plasma lumefantrine concentrations (0.47 mu g/mL; 95% CI, 0.38-0.56 mu g/mL). CONCLUSION: Oral artesunate plus mefloquine and artemether-lumefantrine are highly effective for the treatment of uncomplicated falciparum malaria in Laos.